Kepemimpinan Etnik dan Ketegangan Sosial di Desa Suka Mandi Hilir - Dora, Nuriza; Tambunan, Damai Yanti; Vista, Rizka; Taliba Lubis, Alfiah; Hsb, Sarah Nadia (CV. Ulil Albab Corp, 2025)
This research analyzes ethnic leadership in Suka Mandi Hilir Village and its influence on emerging social tensions among residents. The main objective of this study is to understand how village leaders from majority ethnic groups manage interethnic relationships and address potential conflict in a multicultural setting. The primary method used was a descriptive qualitative approach involving in-depth interviews, participatory observation, and documentation. The findings indicate that unequal representation in leadership contributes to feelings of social exclusion among minority groups, particularly during village head elections. However, the village head’s efforts through interethnic social programs and the role of religious leaders and women’s prayer groups proved effective in mitigating conflict and fostering social cohesion. Village forums remain symbolically exclusive, thus requiring communication reform to ensure equal participation among all residents.